Tungsten–molybdenum fractionation in estuarine environments - Mohajerin, T. Jade; Helz, George R.; Johannesson, Karen H. (Geochimica et cosmochimica acta, 2016)
Dissolved tungsten (W) and molybdenum (Mo) concentrations were measured in surface waters and sediment pore waters of Terrebonne Bay, a shallow estuary in the Mississippi River delta, to investigate the biogeochemical processes that fractionate these Group 6 elements relative to one another during transit from weathering to sedimentary environments. Although many of the chemical properties of W and Mo are similar, the two elements behave autonomously, and the fractionation mechanisms are only partly understood. In sulfidic pore waters, dissolved Mo is depleted relative to river water–seawater mixtures, whereas dissolved W is >10-fold enriched. Reductive dissolution of poorly crystalline phases like ferrihydrite, which is a preferential host of W relative to Mo in grain coatings on river-borne particles, can explain the dissolved W enrichment. Dissolved W becomes increasingly enriched as H2S(aq) rises above about 60μM due to transformation of WO42− to thiotungstates as well as to additional reductive dissolution of phases that host W. In contrast, as rising sulfide transforms MoO42− to thiomolybdates in pore waters, dissolved Mo is suppressed, probably owing to equilibration with an Fe–Mo–S phase. This putative phase appears to control the aqueous ion product, Q=[Fe2+][MoS42−]0.6 [H2S0]0.4/[H+]0.8, at a value of 10−7.78. Concentrations of dissolved W and Mo in pore waters bear no relation to concentrations in surface waters of the same salinity. In surface waters, dissolved Mo is nearly conserved in the estuarine mixing zone. Dissolved W appears also to be conserved except for several cases where W may have been enhanced by exchange with underlying, W-rich pore waters. With increasing salinity, the molar Mo/W ratio rises from about 10 to about 1000 in surface waters whereas it is mostly <10 in underlying pore waters and in highly sulfidic pore waters is mostly near 1. Differences in two chemical properties may account for this fractionation of Mo with respect to W; MoVI is more susceptible to reduction than WVI, but the latter is more prone to adopting octahedral coordination. We propose that the first difference facilitates Mo but not W precipitation in sulfidic sediments, whereas the second explains tungsten’s proportionately greater sequestration on river-borne particles and its subsequent release to sulfidic pore waters after the particles are deposited in the delta and become subject to reductive dissolution during diagenesis.